A Brief History of Chinese Buddhism and Buddhist Thought - Xiuping, HONG, (Asian Studies E-Books Online, Collection 2024., 2024)
This book provides a comprehensive but concise introduction to Chinese Buddhism and the study of Buddhism in China: their Indic roots, their Sinicization, the development and philosophies of the three central lineages, the natural exchange between Buddhist cultures and schools of thought, the foundations of Buddhist studies in China, and the chief schools and sects in Chinese Buddhism as well as their characteristics and ethos.